Analisa Web untuk Memahami Perilaku Konsumen Online Studi Kasus â€œStore Steam Poweredâ€ - Supriyadi, Endang (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2015)
The development of internet users from year to year to date continues to increase, it can be known through a survey conducted Internet Worldstats. According to a survey conducted by Internet Worldstats, United Stated ranks 2nd of internet users worldwide after China. From the results of the survey shows that almost all activities / business activities undertaken by the world population and in particular the citizens of United State / America using internet facilities in all activities, especially transactions online. And one of the tools that can help to analyze online consumer behavior is by using web analytics. The purpose of this paper is to analyze how data analysis can be effectively used to understand current consumer behavior online. Expected with the use of web analytics, companies can predict future consumer behavior online and special messages on promotions that have been sent to each individual. Understanding the patterns and things on the web analytics is expected to help to develop business processes and the contents and design that need to be made especially "store steam powered". Store steam powered is one of Valve's web-based digital distributor. The main service that is done is steam game sales through an e-commerce web that aims to avoid piracy is very rampant at the moment.